Adicción tecnológica y su influencia en el desarrollo psicosocial en niños de 6 años de edad - Zambrano Madrid, Ivonne Elizabeth (2020)
Technological addiction with carries with it psychosocial effects that can be characterized as being positive as well as negative. When a person abuses any type of technology, a psychological disorder may occur as a consequence of the decrease in daily activities and socio-family relationships, the first indications that the child who is addicted to technology may show may be in the need of being connected as long as possible to feel satisfied. If you don't, you feel depressed, nervous, or angry, moods that disappear when you use technology again; first of all, it must be emphasized that, although most children today use technology a lot, that is not synonymous with having an addiction, but it is also true that it is necessary to supervise and be aware of their technological behavior changes to avoid major problems and make sure that there is a balance between your digital life and your life with your family environment.